2022
DOI: 10.1186/s12904-022-00958-9
|View full text |Cite
|
Sign up to set email alerts
|

Inpatient generalist palliative care during the SARS-CoV-2 pandemic – experiences, challenges and potential solutions from the perspective of health care workers

Abstract: Background The SARS-CoV-2 pandemic has presented major challenges to the health system. Despite high acute case numbers, patients without Covid-19 still need to be cared for. Due to the severity of the disease and a possible stressful overall situation, patients with palliative care needs also require comprehensive care during pandemic times. In addition to specialized palliative care facilities, this also takes place in non palliative care wards. In order to ensure this general palliative care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…In this 2 of 10 situation, university research groups from all over Germany founded a joint project named "National Strategy for Palliative Care of Severely Ill and Dying People and their Relatives in Pandemics" (PallPan) [4]. As part of this research group, the Interdisciplinary Center for Palliative Medicine in Duesseldorf conducted a qualitative study to investigate experiences and challenges related to the care of critically ill and dying patients (with or without COVID-19 infection) and their relatives in general inpatient palliative care (PC) [5]. From this study, six critical categories were identified, addressing the following topics: visiting regulations, communication with relatives, hygiene measures, cooperation, determination of the patients' will, and the possibility of saying goodbye [5,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this 2 of 10 situation, university research groups from all over Germany founded a joint project named "National Strategy for Palliative Care of Severely Ill and Dying People and their Relatives in Pandemics" (PallPan) [4]. As part of this research group, the Interdisciplinary Center for Palliative Medicine in Duesseldorf conducted a qualitative study to investigate experiences and challenges related to the care of critically ill and dying patients (with or without COVID-19 infection) and their relatives in general inpatient palliative care (PC) [5]. From this study, six critical categories were identified, addressing the following topics: visiting regulations, communication with relatives, hygiene measures, cooperation, determination of the patients' will, and the possibility of saying goodbye [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…As part of this research group, the Interdisciplinary Center for Palliative Medicine in Duesseldorf conducted a qualitative study to investigate experiences and challenges related to the care of critically ill and dying patients (with or without COVID-19 infection) and their relatives in general inpatient palliative care (PC) [5]. From this study, six critical categories were identified, addressing the following topics: visiting regulations, communication with relatives, hygiene measures, cooperation, determination of the patients' will, and the possibility of saying goodbye [5,6]. Based on our findings, an electronic learning (e-learning) tool was developed within the framework of PallPan to expand the scope of the results and offer interactive support to a larger number of health care workers [4,6].…”
Section: Introductionmentioning
confidence: 99%
“…An investigation of specialist outpatient PC reported changes in the care of patients due to restrictions in visiting hours and highlights the important role of outpatient sPC care in COVID-19 patients not being admitted to hospitals [ 21 ]. Inpatient sPC was also part of the PallPan project [ 23 , 43 , 44 ]. In both general and specialist inpatient PC, the increased hygiene standards with the mandatory personal protective equipment, together with impaired communication, restricted visiting hours and hampered interdisciplinary cooperation, were considered burdensome [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Inpatient sPC was also part of the PallPan project [ 23 , 43 , 44 ]. In both general and specialist inpatient PC, the increased hygiene standards with the mandatory personal protective equipment, together with impaired communication, restricted visiting hours and hampered interdisciplinary cooperation, were considered burdensome [ 23 ]. Overall, the PallPan project addressed multiple aspects of PC such as the infrastructure, patients with and without COVID-19, the relatives, mourning and the healthcare professionals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation